IFC and its role in globalization : highlights from IFC's participants meeting, Washington, D.C., June 6-7, 2001 - Lazarus, Suellen Lambert; International Finance Corporation (Washington, D.C. : World Bank : International Finance Corporation, 2002)
This title is based upon the 2001 the International Finance Corporation Participants Meeting. The focus of this meeting was the IFC's role in globalization, examining globalization from the perspective of its ability to influence and change global affairs as well as its role in poverty alleviation.
osc 2/9/16
Loans
Keywords: International Finance Corporation; Globalization